A study of female Middle Eastern entrepreneurs: a resource-based view. Issue 1 (10th July 2017) - Khizindar, Tariq M.; Darley, William K.
Abstract : Purpose: Using the resource-focused view of the firm as a theoretical backdrop, this study aims to examine the relationships between entrepreneurial perceptions and two dependent measures (i.e. customer satisfaction outcomes and firm performance). Specifically, the study tests the boundary conditions of the resource-based view (RBV) performance relationship in a Middle Eastern context. Design/methodology/approach: The data from 171 female Saudi entrepreneurs are analyzed using structural equation modeling. Findings: The research results revealed that marketing capability and financial capability (i.e. financial capital access) have a positive significant effect on both dependent measures. Labor shortage also has a negative significant effect on both dependent variables, whereas operations capability does not show a significant effect on the two dependent measures. To a large extent, the results show that the RBV holds true in the Saudi context. Originality/value: The study contributes to the knowledge about the effects of specific human and financial capital, as well as illuminates how marketing capability, financial capital access and labor shortage impact these dependent variables in the unique context of Saudi Arabia among female entrepreneurs, thereby extending the knowledge of the RBV in different contexts. Furthermore, it extends knowledge of the entrepreneurship literature, especially in the area of gender-based entrepreneurship research in developing countries.